Practical Biometrics From Aspiration to Implementation - Ashbourn, Julian (Springer, 2015)
Biometric verification techniques have been available for many years. Although the principle of using a biometric can be traced back to ancient times, the concept of commercially available devices with which to automate biometric identity verifica tion was effectively a product of the late 1960s, with further development through the 1970s and 1980s leading to a step up in interest in the late 1980s. By the early 1990s, there were a raft of biometric device manufacturers offering a range of tech niques including hand geometry , retinal scanning , fingerprints , voice verification , signature verification, and facial recognition . These were soon to be complemented by iris recognition, finger geometry, vein recognition, and other techniques, providing an intriguing technology choice for early adopters...